The effect of cigarette smoking on endothelial damage and atherosclerosis development – modeled and analyzed using Petri nets - Chmielewska, Kaja; Formanowicz, Dorota; Formanowicz, Piotr (Archives of Control Sciences, 2017)
Abstract Atherosclerosis as one of the crucial causes of cardiovascular diseases (CVD) is the leading reason of death worldwide. One of the contributing factors to this phenomenon is endothelial dysfunction, which is associated with the impact of various agents and their interactions. Tobacco smoke is one of the well known factors here. For better understanding of its significance a model of its impact on atherosclerotic plaque formation has been proposed. The model contains selected aspects of the influence of tobacco smoke, dual function of nitric oxide (NO) (influence of various mechanisms on NO bioavailability), oxidative stress which promotes low density lipoproteins oxidation, macrophages significance and other mechanisms leading to an aggravation of the endothelial disturbances. The model has been built using Petri nets theory and the analysis has been based on t-invariants. This approach allowed to confirm the important role of inflammation and oxidative stress in atherosclerosis development and moreover it has shown the considerable influence of the cigarette smoke.